Tratamiento contable de propiedad, planta y equipo en el GAD Municipal del cantón Montalvo - Sánchez Medina, Wilhelm Fernando (2021)
This case study was carried out based on the Accounting Treatment of Property, Plant and Equipment given by the Municipal GAD of the Montalvo Canton, which as a public entity is governed by the policies established by the Ministry of Economy and Finance through its regulations and what is established by the Comptroller General of the State in its regulations for the correct management of its assets. This investigation was directed specifically to the items of vehicles and machinery in which deficiencies were found at the time of canceling or calculating their useful life, which generates a bad record in their balance sheets. Thus, during the development of the investigation it was found that some machinery had been given the wrong useful life, which generated erroneous data in the accumulated depreciation values and book value. Another inconvenience that generates an anomaly within the institution is that during the transition of authorities the closing of the accounting books has not been carried out adequately and the information that has been provided has many inconsistencies. The methodology used for the development of this case study is analytical, descriptive in order to proceed to interpret and analyze the information provided on the inventories of Property, plant and equipment, focusing on the Financial Management sub-line of research.